The production of “Ethno-commodities” in the atacameños tourism context (Revista LIDER, 2020)
For ten years now, atacameño communities have taken over the administration of patrimonial resources. This article analyzes three tourism experiences developed by social organizations of the Salar de Atacama. As a consequence of the incorporation of the ethnic minority in the tourist industry, processes of cultural change and the production of “ethno commodities” are being generated.